Discourse and leadership of Dr. Mahathir Mohamed: The relational value of texts to create solidarity - Ghazali, Kamila (Journal of Modern Languages, 2017)
Dr. Mahathir Mohamed has been hailed as one of the most effective orators in the world. His speeches have been targeted at various levels of audiences at home and abroad. How does the discourse differ as he relates to the different target audiences? This paper focuses on the discourse generated by the Malaysian Prime Minister during the keynote addresses at the annual general assembly of the ruling party, UMNO from 1982-1996. Specifically, the paper investigates the discourse employed by the speaker to form relations of solidarity with the different layers of society in Malaysia. The theoretical framework adopted is a version of Critical Discourse Analysis (CDA) as provided by Norman Fairclough (1989). CDA focuses on the social effects of discourse as discourse is socially shaped and in turn re-shapes societal formations.